Human capital impact on China-ASEAN cross-border trade / Lanlan Yang ... [et al.] - Yang, Lanlan; Yassin, Jain; Niasin, Mohd Adzwin Faris; Fudong, Gao (Universiti Teknologi MARA Cawangan Sarawak, 2024)
With the implementation of the Belt and Road Initiative and RCEP, the economic and trade cooperation between China and ASEAN is deepening, and the position of China and ASEAN countries in their cross-border trade is becoming increasingly important. In international trade and its division of labour, the impact of a country's human capital on its trade development is crucial. This article uses panel data between China and ASEAN from 2000 to 2021 and uses a fixed effects gravity model to analyse the impact of human capital factors on China-ASEAN cross-border trade. The results show that human development index has a significant negative effect on ASEAN imports from China, but significant promoting effect on ASEAN exports to China. The tertiary level enrolment has an insignificant negative effect on ASEAN imports from China, and an insignificant promoting effect on ASEAN exports to China. Policy recommendations were proposed based on the results.